Mastering the New Testament ; v. 7 - Chafin, Kenneth L. (Dallas, TX Word, 1985)
Contents : v. 7 : 1,2 Corinthians. Includes bibliographical references.
Keywords: Bible. N.T. Corinthians -- commentaries